Comparison of clinicopathological characteristics and prognosis among patients with pure invasive ductal carcinoma, invasive ductal carcinoma coexisted with invasive micropapillary carcinoma, and invasive ductal carcinoma coexisted with ductal carcinoma in situ: A retrospective cohort study. Issue 50 (11th December 2020) - Guan, Xin; Xu, Guiying; Shi, Aiping; Zou, Yabin; Zhan, Yue; Fan, Zhimin; Dong, Yi
Abstract : Abstract: This paper aimed to analyze the clinicopathological characteristics of invasive ductal carcinoma with an invasive micropapillary carcinoma component (IDC + IMPC), invasive ductal carcinoma with a ductal carcinoma in situ component (IDC + DCIS), and compare the clinicopathological characteristics and prognosis to those of IDC. A total of 1713 patients (130 IDC + IMPC cases, 352 IDC + DCIS cases, and 1231 pure IDC cases) who underwent appropriate surgery from June 2011 to September 2017 were retrospectively selected. Compared to the pure IDC and IDC + DCIS patients, the IDC + IMPC patients presented with more aggressive characteristics, such as a higher proportion of vascular invasion ( P  < .001), fewer progesterone receptor (PR)-positive patients ( P  < .001), a lower proportion of cases in American Joint Committee on Cancer stage I ( P  < .001), a higher recurrence risk ( P  < .001), more deaths ( P  < .001), and more metastatic cases ( P  < .001). Compared to the pure IDC and IDC + IMPC patients, the IDC+DCIS patients presented with less aggressive characteristics, such as a higher proportion of estrogen receptor-positive patients ( P  < .001) and PR-positive patients ( P  < .001), a lower proportion of cases with nerve invasion ( P  < .001) and vascular invasion ( P  < .001), a higher proportion of cases in American Joint Committee on Cancer stage I ( P  < .001), fewer deaths ( P  < .001), and fewer metastatic cases ( P  < .001). The patients with IDC + DCIS had significantly better disease-free survival (DFS) and overall survival (OS) compared to those with pure IDC and IDC + IMPC ( P  < .001). The patients with IDC + IMPC had significantly worse DFS and OS compared to those with pure IDC and IDC + DCIS ( P  < .001). In univariate analysis, the presence of an IMPC component in IDC ( P  = .007), estrogen receptor status ( P  = .05), and PR status ( P  = .003) were factors associated with OS. In multivariate analysis, coexisting IMPC ( P  = .04) was the only independent prognostic factor associated with OS. Compared to IDC and IDC + DCIS, IDC + IMPC had more aggressive characteristics and significantly worse DFS and OS. Compared to IDC and IDC + IMPC, IDC + DCIS had less aggressive characteristics and significantly better DFS and OS.